Diagnóstico e formulação de políticas públicas em municípios abaixo de 50 mil habitantes: recomendações e instrumentos - Miguel, Juarez Viqueira (2012)
Discussions on the use of indicators in public policy formulation have increased its relevance in the national context. The federal and state governments are encouraging, based on its current initiatives, local authorities to develop diagnosis and adopt planning for the realities they intend to interfere. In this sense, the importance of using information to enhance the effects in all public policy cycle, including diagnosis, formulation, execution and evaluation, has become clear. One of the challenges surrounding the issue is to conceive adequate instruments to support local authorities in small cities to develop diagnosis based on structured knowledge on reality. The present work intends to contribute to this debate through recommendations aiming at improving one of the existing instruments currently in use: the publication 'Construindo o diagnóstico municipal: uma metodologia' ['Developing the municipal diagnosis: a methodology']. This publication was developed in 2008 by the Center for the Study and Research of Local Administration (CEPAM, in the Portuguese acronym) and the Institute of Economics of the University of Campinas with the objective of providing the mayors that had just taken office proper conditions to obtain basic information relevant to the development of municipal planning. Four years after the launch of the publication, the staff of CEPAM is willing to publish a second edition of the document, directed at small cities, which justifies the purpose of this work in providing recommendations for its improvement. To that end, the group of researchers involved in the work has used three research instruments: critical analysis of CEPAM’s publication, interviews with mayors of small cities and qualitative interviews with experts from institutions that produce and disseminate data. Overall, we have made interviews with 22 mayors and 9 experts in public policy diagnosis and analyzed around 250 indicators with multidimensional scope. The results of the over 30 interviews that have taken place point out to a series of particularities that obstacle the use of diagnosis by small local administrations. Based on the content of these hurdles and findings identified, we have mapped the most relevant issues, which were classified in four areas of intervention and 14 recommendations to support CEPAM in revising the publication to be disseminated to cities with less than 50 thousand inhabitants.